Analyse of the early effects on the Ukrainian forestry sector as a result of the Log Export ban : an interview study with economic analyses, including theories about trade and export - Olsson, Magdalena (SLU/Dept. of Forest Products, 2017)
Illegal logging and illegal export of roundwood has been of great concern within the forestry sector around the whole world for a long time. One of the most common tools used in hopes to resolve this issue is a law called The Log Export Ban (LEB). When the government in a country implements this law, it means that the country is no longer allowed to export unprocessed wood. This has a drastic effect on the country itself, but also surrounding countries that has been dependent on import of the unprocessed wood. The aim of the law is however to help the country develop its national processing industry, create more job opportunities and this way increase the national income. The hope is also that a LEB will reduce the amount of illegal cutting and over harvest. Ukraine has been suffering from these issues and therefore the parliament decided to insert an export ban on all roundwood, except pine, starting in November 2015 and for pine starting from January 2017. This field study, conducted from April- May 2016, aims to analyse the early effects of the LEB in Ukraine, based on the national forest organisations perspective.